2023
DOI: 10.3390/plants12030523
|View full text |Cite
|
Sign up to set email alerts
|

Do Tree Size and Tree Shade Tolerance Affect the Photosynthetic Capacity of Broad-Leaved Tree Species?

Abstract: (1) Background: leaf structure traits are closely related to leaf photosynthesis, reflecting the ability of trees to obtain external resources in the process of growth. (2) Methods: We studied the morphological, chemical, anatomical, stomatal traits and maximum net photosynthetic rate of six broad-leaf species in northern temperate mixed broad-leaved Korean pine (Pinus koraiensis) forest. (3) Aim: To investigate whether there are differences in leaf structural traits of trees with different shade tolerances an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 68 publications
2
6
0
Order By: Relevance
“…A decrease in the total amount of chlorophyll was determined in parallel with the increasing salt dose. Similar results were found in studies (Ru et al, 2023;Song et al, 2023). Chlorophyll content directly affects photosynthesis (Nalley et al, 2023) and is accepted as an indicator of photosynthetic capacity in tissues (Song et al, 2023).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…A decrease in the total amount of chlorophyll was determined in parallel with the increasing salt dose. Similar results were found in studies (Ru et al, 2023;Song et al, 2023). Chlorophyll content directly affects photosynthesis (Nalley et al, 2023) and is accepted as an indicator of photosynthetic capacity in tissues (Song et al, 2023).…”
Section: Resultssupporting
confidence: 84%
“…Similar results were found in studies (Ru et al, 2023;Song et al, 2023). Chlorophyll content directly affects photosynthesis (Nalley et al, 2023) and is accepted as an indicator of photosynthetic capacity in tissues (Song et al, 2023). Since the high photosynthetic activity will increase the production of the substance, it also increases the yield (Ru et al, 2023).…”
Section: Resultssupporting
confidence: 82%
“…One explanation for this observation is that larger trees experience greater water stress as a consequence of being taller, which requires a greater hydraulic connectivity (Mencuccini, 2003;Ryan et al, 1997Ryan et al, , 2006Sala & Hoch, 2009;Song & Jin, 2023). However, the statistically insignificant relationship observed between PFM and LFM scaling exponents between the two groups is not in agreement with the expectation that the scaling exponents would differ between the two tree size groups (Figure 5b).…”
Section: The Scaling Exponents Governing Lamina Size and Petiole Size...mentioning
confidence: 79%
“…Along these lines, some studies have shown that the leaves of larger trees reduce water potential by increasing the input of solutes such as starch and lipids to obtain sufficient water, resulting in an increase in lamina mass per unit area (Sala & Hoch, 2009;Song & Jin, 2023).…”
Section: Diminishing Returns Of La Versus Lamina Mass In the Two Tree...mentioning
confidence: 99%
See 1 more Smart Citation